2008
DOI: 10.1007/s10461-008-9403-3
|View full text |Cite
|
Sign up to set email alerts
|

Drug Use, High-Risk Sex Behaviors, and Increased Risk for Recent HIV Infection among Men who Have Sex with Men in Chicago and Los Angeles

Abstract: We examined how drugs, high-risk sexual behaviors, and socio-demographic variables are associated with recent HIV infection among men who have sex with men (MSM) in a case-control study. Interviewers collected risk factor data among 111 cases with recent HIV infection, and 333 HIV-negative controls from Chicago and Los Angeles. Compared with controls, cases had more unprotected anal intercourse (UAI) with both HIV-positive and HIV-negative partners. MSM with lower income or prior sexually transmitted infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
1
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(122 citation statements)
references
References 50 publications
(73 reference statements)
4
108
1
9
Order By: Relevance
“…2,3 Prior studies with MSM have also found a strong association between substance use and UAS, yet the casual link between these two behaviors regarding HIV acquisition is much less understood and critically important for HIV prevention. [3][4][5][6][7][8][9][10][11][12][13][14][15] Two recent and substantive literature reviews describe how assessment of substance use with or without sex among MSM has been inconsistent among prior studies. 16,17 Despite these inconsistencies, several key themes were noted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Prior studies with MSM have also found a strong association between substance use and UAS, yet the casual link between these two behaviors regarding HIV acquisition is much less understood and critically important for HIV prevention. [3][4][5][6][7][8][9][10][11][12][13][14][15] Two recent and substantive literature reviews describe how assessment of substance use with or without sex among MSM has been inconsistent among prior studies. 16,17 Despite these inconsistencies, several key themes were noted.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Studies have also documented characteristics of MSM who use illegal (e.g., methamphetamines) and prescription drugs (e.g., erectile dysfunction medications (EDM)) with sex as gay, white, and/or 40 years of age and older. 5,7,[20][21][22] Younger MSM (i.e., 29 and younger) have also been shown to use substances with sex, and differences in substance use with sex may also exist based on the HIV status of MSM. [23][24][25] Studies have noted that HIV-positive MSM are more likely to use party drugs (e.g., cocaine, ecstasy, ketamine, gammahydroxybutrate (GHB), methamphetamine) and prescription drugs, including EDM and sleep aids, than HIV-negative MSM.…”
Section: Introductionmentioning
confidence: 99%
“…This was attributed to a "nothing left to lose" attitude. While HIV-positive men have been reported as more likely to use crystal meth and engage in IDU than HIV-negative men (Bonell, Hickson, Weatherburn, & Reid, 2010;Bourne et al, 2014;Carey et al, 2009;Forrest et al, 2010) it is also the case that both are minority behaviours among men with diagnosed HIV.…”
mentioning
confidence: 99%
“…Although previous studies found a significant relationship between HIV risk-related behavior and a reported history of CSA, this study did not confirm such a relationship. It may be that this type of relationship is indirect and complex, requiring another deterministic mechanism that lies outside the scope of this study [51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%